Analysis Perceptions Performance of Geography Subject Teachers of Public and Private High Schools in Jombang District (Within the Scope of the Professional Phase Before and After Teacher Certification) - Christyanto, Theofilus Brian; Utomo, Dwiyono Hari (Future Space: Studies in Geo-Education, 2024)
In the current era, the development of education has undergone many transformative changes, such as the integration of technology in learning processes, improvements in educational facilities, innovative teaching methods, and a shift in teachers' paradigms towards professionalism. This study aims to assess the professional status of geography teachers in public and private high schools in Jombang Regency and analyze how teachers' perceptions of professional development phases influence their performance. Data collection methods included observations, questionnaires, interviews, and documentation to provide a comprehensive analysis. The results indicate that geography teachers in both public and private schools exhibit varying levels of professional competence, with notable differences influenced by their perceptions of professional development. Teachers with a positive view of professional growth phases tend to perform better in teaching and student engagement. The discussion elaborates on these findings, highlighting the importance of continuous professional development and supportive institutional policies to enhance teacher performance and educational outcomes.